(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Neonatal sepsis is a clinical syndrome resulting from the pathophysiologic effects of local or systemic infection. It is one of the major cause of morbidity and mortality of neonate and is an enduring major global public health challenge predominantly in developing countries. The objective of this study is to evaluate the risk factors association with neonatal sepsis in tertiary care hospital of Chattagram Maa Shishu O General Hospital (CMSOGH), Chattogram. Materials and methods: The study was a prospective type of case control study, conducted from October to December 2023, in the tertiary care hospital of Chattogram. A total sample 150 were selected, among them 50 cases, were proven sepsis through clinical and laboratory criteria of IMNCI (Integrated Management of Neonatal and Childhood Illness were incorporated as cases in this study. Those were neither suspected nor diagnosed sepsis but admitted to the Neonatal Ward of CMSOGH due to other indications such as low birth weight, neonatal jaundice, diarrhea etc. throughout the study period were included as controls. The chi square test was used to test the association between dependent and independent variables associated with risk factors to neonatal sepsis. Results: Late onset neonatal sepsis was common among neonatal sepsis and maternal age<20 years and mode of delivery, who were delivered by vaginalyhad significant association of sepsis. Maternal history of UTI (Urinary Tract Infection) in 3rd trimester and mode of delivery were significant (p<0.05) as a risk factors of sepsis. APGAR score <7 and prematurity both p-value <0.05, that’s indicate significant association with neonatal sepsis. The common presenting symptoms among the neonates were jaundice and refusal to feed. The organisms isolated were Acinetobacter (30%) Pseudomonas (30%) Klebsiella (20%) Coagulate negative staphylococcus aureus (15%). Conclusion: The study concludes that maternal age, UTI in 3rd trimester, mode of delivery and low APGAR score were high risk factors for neonatal sepsis. Ensuring proper antenatal care employment would help early recognize the risk factors of neonatal sepsis and applicable intrusions for achievement of SDG (Sustainable Development Goals) where neonatal mortality is a burning issue to resolve as part of sustainable development in medical science of a country. JCMCTA 2024 ; 35 (2) : 156-163